2021
DOI: 10.1038/s41419-021-04283-6
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of soluble epoxide hydrolase suppressed chronic kidney disease-related vascular calcification by restoring Sirtuin 3 expression

Abstract: Vascular calcification is common in chronic kidney disease (CKD) and contributes to cardiovascular disease (CVD) without any effective therapies available up to date. The expression of soluble epoxide hydrolase (sEH) is different in patients with and without vascular calcification. The present study investigates the role of sEH as a potential mediator of vascular calcification in CKD. Both Ephx2−/− and wild-type (WT) mice fed with high adenine and phosphate (AP) diet were used to explore the vascular calcifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…One of the important functions of sEH is metabolizing epoxyeicosatrienoic acids (EETs), which is an anti-inflammatory substant. Based on the protective properties of EETs, inhibition of sHE is a potential target for kidney protection ( Manhiani et al, 2009 ; Greite et al, 2020 ; Lin et al, 2020 ; He et al, 2021 ). However, the exact functions of six RFRGs in the kidney still need further study.…”
Section: Discussionmentioning
confidence: 99%
“…One of the important functions of sEH is metabolizing epoxyeicosatrienoic acids (EETs), which is an anti-inflammatory substant. Based on the protective properties of EETs, inhibition of sHE is a potential target for kidney protection ( Manhiani et al, 2009 ; Greite et al, 2020 ; Lin et al, 2020 ; He et al, 2021 ). However, the exact functions of six RFRGs in the kidney still need further study.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenesis of vascular calcification is complex. Recent studies on vascular imaging, cell biology, and molecular biology have suggested that vascular calcification is a cell-mediated active and highly controllable biological process [ 26 ]. CAC promotes cardiovascular event occurrence and development [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of SIRT3 might induce an increase in the acetylation of PGC-1α, leading to PGC-1α dysfunction, which also compromised mitochondrial adenosine triphosphate (ATP) production and morphology damage, ultimately triggering VSMCs phenotypic transition and calcium deposition. Furthermore, deletion of soluble epoxide hydrolase was reported to stabilize and increase SIRT3, thereby ameliorating mitochondrial abnormalities and VC in CKD or high phosphate conditions ( 78 ). Currently, berberine, honokiol, and resveratrol have been confirmed to target SIRT3 to correct pathological condition.…”
Section: Sirtuins and Vascular Calcificationmentioning
confidence: 99%